CURRICULUM ORGANIZATION - Muhammad Mukhlis Anshori; Mohammad Nuzulul Qodri Arif; Muhammad Chusaini Alfin (Fakultas Ilmu Pendidikan Universitas Negeri Surabaya, 2023)
Curriculum organization has an important role in facilitating students to learn subject matter, thereby achieving effective learning objectives. Curriculum organization, i.e. the pattern or form of learning materials compiled and delivered to students which is a very important basis in curriculum development and is closely related to the goals of the educational program to be achieved, because the form of the curriculum also determines the learning materials, their sequence and how to present them to students/learners. This study uses the method of library research (library research) which takes data sources from relevant theories. The data sources in this study are the subject of valid and relevant data using primary data collection techniques with updated and online documentation, as well as supporting or secondary data by seeking the latest sources, whether in the form of books, articles, or websites. The results of this study are a discussion of the concept of curriculum organization, principles of curriculum organization, vertical curriculum organization, and horizontal curriculum organization.